Gatley on libel and slander (Sweet & Maxwell LondonGB, 2004)
Deals with the English law of defamation and jurisprudence of the European Court of Human Rights. Focuses on procedure.\n
Located in the Office of General Counsel.\n Located in the Office of General Counsel.\n